Governmental Inter-sectoral Strategies to Prevent and Control COVID-19 in a Megacity: A Policy Brief From Shanghai, China - He, Xiaolin; Jiang, Ping; Wu, Qiong; Lai, Xiaobin; Liang, Yan (Frontiers in Public Health, 2022)
This policy brief aims to help policymakers develop inter-sectoral interventions in megacities to prevent and control COVID-19. Based on the case of Changning District in Shanghai, China, several policy options are identified. The guiding principles include ensuring a coordinated national response (i.e., moderation is required in epidemic prevention and control); making science-based, precise, and differentiated epidemic control strategies; and establishing a joint prevention and control mechanism. Policy tools include localized management, closed-loop management, community grid management, digital management, and sub-population management. There is no “one size fits all” policy; however, it will be helpful to learn by trial and error through on-the-ground experience with minimal information in real time.